2001
DOI: 10.1021/es001441l
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Removal of Zinc from Composted Municipal Solid Wastes

Abstract: This paper presents composting of the organic fraction of municipal solid waste containing 50,000 mg/kg of cellucotton and 7980 mg/kg of zinc carried out under laboratory conditions. In the initial material as well as the compost obtained, zinc, cadmium, copper, nickel, and lead were analyzed, and their forms were determined by means of sequential extraction. It was found that 65% of zinc occurs in the organically bound form. Removal of zinc from the waste through leaching and subsequent electrochemical separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…3,4 More recently, these procedures have been applied to compost. [5][6][7][8] It has also been shown that this timeconsuming process can be speeded up substantially if an ultrasonically accelerated version of sequential extraction is utilized. 9 Using this rapid method it was found that elements such as Zn, Mn and As had a high potential mobility in compost, whereas other elements such as Pb, Cu, Fe, and Cr exist mainly in immobilized forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 More recently, these procedures have been applied to compost. [5][6][7][8] It has also been shown that this timeconsuming process can be speeded up substantially if an ultrasonically accelerated version of sequential extraction is utilized. 9 Using this rapid method it was found that elements such as Zn, Mn and As had a high potential mobility in compost, whereas other elements such as Pb, Cu, Fe, and Cr exist mainly in immobilized forms.…”
Section: Introductionmentioning
confidence: 99%
“…15 Compost may therefore have to be cleaned up before application to land or even before the composting process has been carried out. 7 One way to clean up the compost is to use a flushing technique with leaching reagents. This approach has been more frequently investigated for cleaning heavy metal contaminated soil.…”
Section: Introductionmentioning
confidence: 99%